2019
DOI: 10.1158/0008-5472.can-18-2086
|View full text |Cite
|
Sign up to set email alerts
|

ERBB3 and IGF1R Signaling Are Required for Nrf2-Dependent Growth in KEAP1-Mutant Lung Cancer

Abstract: Mutations in KEAP1 and NFE2L2 (encoding the protein Nrf2) are prevalent in both adeno and squamous subtypes of non-small cell lung cancer, as well as additional tumor indications. The consequence of these mutations is stabilized Nrf2 and chronic induction of a battery of Nrf2 target genes. We show that knockdown of Nrf2 caused modest growth inhibition of cells growing in two-dimension, which was more pronounced in cell lines expressing mutant KEAP1. In contrast, Nrf2 knockdown caused almost complete regression… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 32 publications
1
11
0
Order By: Relevance
“…The pathway analyses of this study also revealed that PI3K/Akt pathway was enriched in the P2 subgroup. Vartanian et al identi ed alternative pathways critical for NFE2L2-dependent growth in KEAP1-mutant cell lines, including IGF1R [33]. The ndings in this study suggested that inhibitors of IGF1R signaling were effective in the C2 subtype.…”
Section: Discussionmentioning
confidence: 51%
“…The pathway analyses of this study also revealed that PI3K/Akt pathway was enriched in the P2 subgroup. Vartanian et al identi ed alternative pathways critical for NFE2L2-dependent growth in KEAP1-mutant cell lines, including IGF1R [33]. The ndings in this study suggested that inhibitors of IGF1R signaling were effective in the C2 subtype.…”
Section: Discussionmentioning
confidence: 51%
“…As XQ‐2d‐His‐SH2 CM‐(Arg)9 and His‐SH2 CM‐(Arg)9 exhibited similar pY‐binding and inhibitory ability in vitro as previously identified in Figure 2G, we utilized His‐SH2 CM‐(Arg)9 to investigate whether SH2 superbinder could block signal transduction in pY‐related pathways. Dysregulation in activity of EGFR, IGF‐1R, and VEGFR is highly correlated with a lot of cancers 54–56 . The enhanced affinity between SH2 superbinder and the pY implied that they may function as an inhibitor of pY‐based signaling pathways.…”
Section: Resultsmentioning
confidence: 99%
“…Dysregulation in activity of EGFR, IGF-1R, and VEGFR is highly correlated with a lot of cancers. [54][55][56] The enhanced affinity between SH2 superbinder and the pY implied that they may function as an inhibitor of pY-based sig-naling pathways. To test this hypothesis, we incubated the PANC-1 WCLs with His-SH2 CM-(Arg)9, His-SH2 Wt-(Arg)9, and His-(Arg)9, respectively.…”
Section: Xq-2d-his-sh2 Cm-(arg)9 Influenced Multiple Signaling Cascadmentioning
confidence: 99%
“…Li et al described that EZH2 (enhancer of zeste homolog 2) inhibits lung cancer growth both in vitro and in vivo, and it does so by binding and repressing the NFE2L2 promoter [125]. Additionally, tyrosine kinase receptors, such as insulin-like growth factor 1 receptor (IGF1R) and erb-B2 receptor tyrosine kinase 3 (ERBB3), were recently discovered to be also important for KEAP1-mutant lung cell growth [126]. Krall et al showed that KEAP1 loss is involved in the resistance of NSCLC cell lines with mutations in EGFR, ALK, B-RAF and K/N-RAS to selective inhibitors of these kinases [127].…”
Section: Bad Side Of Nrf2 In Nsclc Progressionmentioning
confidence: 99%